2020
DOI: 10.13057/biodiv/d211228
|View full text |Cite
|
Sign up to set email alerts
|

The predator-prey model on squids and anchovies fisheries in Jepara District, Central Java, Indonesia

Abstract: Abstract. Wijayanto D, Bambang AN, Kurohman F. 2020. The predator-prey model on squids and anchovies fisheries in Jepara District, Central Java, Indonesia. Biodiversitas 21: 5698-5703. Traditional fisheries dominate marine fisheries in Jepara District, Central Java, Indonesia, including the lift net. The catch of the lift net includes squids and anchovies. The ecological relationship between squids and anchovies must be investigated to develop squids and anchovies management. Without proper modeling, the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition to its high cruising ability, it is also capable of predating various types of prey, so it has the potential to be used as a pest control agent with a high personality. The research results of [50] indicated two types of predators with high potential to suppress B. tabaci populations in the field were Coccinella sp. and Paederus fuscipes because every 24 hours, they are able to predate up to 41 B. tabaci nymphs while the predation ability of imago is around 10-17 individuals.…”
Section: The Abundance Of Natural Enemies Populationsmentioning
confidence: 99%
“…In addition to its high cruising ability, it is also capable of predating various types of prey, so it has the potential to be used as a pest control agent with a high personality. The research results of [50] indicated two types of predators with high potential to suppress B. tabaci populations in the field were Coccinella sp. and Paederus fuscipes because every 24 hours, they are able to predate up to 41 B. tabaci nymphs while the predation ability of imago is around 10-17 individuals.…”
Section: The Abundance Of Natural Enemies Populationsmentioning
confidence: 99%
“…The other gears that caught a significant proportion of these families by weight were troll line (98.7%), dropline (93.4%), set gillnet (53.7%), and trap (100%). Although epinephelids and lutjanids were landed using boat liftnets, these data were omitted from further analysis, as this fishing method is primarily used to target anchovies and other bait fish [55,56].…”
Section: Overall Catch Compositionmentioning
confidence: 99%
“…Many studies on artisanal fisheries in Java have been carried out, and Selaroides (Wijayanto et al 2019a, Wijayanto et al 2019b) is one of the catch targets for medium-sized nets such as the use of Danish seine fishing gear, which is considered an environmentally friendly fishing gear compared to trawling (Adhawati et al 2017a, Adhawati et al 2017b). This artisanal fishery has driven the economy and even continues today.…”
Section: Sub-family Caranginaementioning
confidence: 99%
“…For example, capture fisheries in Pekalongan with mini purse seine fishing gear that get catches belonging to the Caranginae group, such as the type of Decapterus sp (Maulana et al 2017). In addition, artisanal fisheries in the northern waters of Java are also highly developed, such as in Banten (Barlian et al 2020;Barlian et al 2021), Tegal (Wijayanto et al 2019a), Lamongan (Syamsuddin et al 2020), and Madura (Yonvitner et al 2021).…”
Section: Sub-family Caranginaementioning
confidence: 99%